2022
DOI: 10.1111/apt.17309
|View full text |Cite
|
Sign up to set email alerts
|

Faecal microbiota transplantation for recurrent C. difficile infections: challenges and improvement opportunities for clinical practice and healthcare systems

Abstract: Summary Background There is growing interest in faecal microbiota transplantation (FMT) as a treatment for recurrent Clostridioides difficile infection (CDI), but evidence on the diverse requirements for safe, effective and accessible services is fragmented and limited. Aims To identify key components of FMT provision relating to the patient care pathway, stool donor pathway and wider healthcare system, and to explore variation in practice Methods We conducted a narrative review of the literature and consultat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…FMT helps re‐establish the balance of GM, repair the intestinal mucosal barrier, control inflammatory responses, and regulate host immunity 135 (Figure 5 ). Numerous studies have confirmed the effectiveness and safety of FMT for treating recurrent Clostridium difficile infections, 136 IBDs, 137 and other gastrointestinal diseases. FMT can modulate neurological disorders driven by dysbiosis, and it may enhance neural regeneration in mice with spinal cord injury by restraining blood‐spinal cord barrier damage, upregulating neurotrophic factors, alleviating spinal cord ischemia, and promoting neuronal survival 138 , 139 (Table 2 ).…”
Section: Treatment Of Brain Injury In Preterm Infants Mediated Throug...mentioning
confidence: 98%
“…FMT helps re‐establish the balance of GM, repair the intestinal mucosal barrier, control inflammatory responses, and regulate host immunity 135 (Figure 5 ). Numerous studies have confirmed the effectiveness and safety of FMT for treating recurrent Clostridium difficile infections, 136 IBDs, 137 and other gastrointestinal diseases. FMT can modulate neurological disorders driven by dysbiosis, and it may enhance neural regeneration in mice with spinal cord injury by restraining blood‐spinal cord barrier damage, upregulating neurotrophic factors, alleviating spinal cord ischemia, and promoting neuronal survival 138 , 139 (Table 2 ).…”
Section: Treatment Of Brain Injury In Preterm Infants Mediated Throug...mentioning
confidence: 98%
“…This article is linked to Hocking et al paper. To view this article, visit https://doi.org/10.1111/apt.17309 Ayushi Chauhan 1 Mayur Garg 1,2…”
Section: N K Ed Co Ntentmentioning
confidence: 99%
“…We read with interest the paper by Hocking et al 1 regarding the numerous challenges of faecal microbiota transplantation (FMT) provision for patients with Clostridioides difficile ( C. difficile ) infection. We congratulate them for a comprehensive synthesis using a variety of literature searches and interviews with selected clinical experts from four high‐income countries.…”
mentioning
confidence: 99%
“…Fecal microbiota transplantation (FMT) is a cutting-edge therapy for treating diseases related to gut dysbiosis, whereby a fecal sample from the patient before treatment (autologous) or from a healthy donor (allogeneic) is transferred to a recipient with a disease condition. Although most of the available evidence has focused on FMT as a treatment for recurrent Clostridioides difficile infection [49], recent studies have begun to investigate its potential as a promising therapeutic strategy for cancer cachexia.…”
Section: Interventions Targeting the Gut Microbiota In Cancer Cachexiamentioning
confidence: 99%